2005
DOI: 10.4028/www.scientific.net/msf.475-479.755
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Ni<sub>3</sub>Al for Hydrogen Production Reactions

Abstract: Ni3Al has attractive high temperature properties, such as high strength and good oxidation/corrosion resistance, and is possible to be used for high temperature chemical processing and manufacture. Until now, the catalytic properties of Ni3Al were rarely investigated since the leaching of aluminum from Ni3Al is difficult to obtain a porous Raney-Ni compared to NiAl3 and Ni2Al3. In the present work, the catalytic properties of Ni3Al were examined for hydrogen production reactions from methanol. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Our previous TEM observation revealed that each band had a single brass texture [11]. Thus, two kinds of bands, (110) [-112] and (110) [1][2][3][4][5][6][7][8][9][10][11][12], which were alternately located in the transverse direction, formed the dual Brass textures in total.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous TEM observation revealed that each band had a single brass texture [11]. Thus, two kinds of bands, (110) [-112] and (110) [1][2][3][4][5][6][7][8][9][10][11][12], which were alternately located in the transverse direction, formed the dual Brass textures in total.…”
Section: Resultsmentioning
confidence: 99%
“…We have developed Ni 3 Al foils for high-temperature micro chemical devices [1][2][3][4][5][6]. For the application there are serious concerns about the brittleness in the foils, especially in the recrystallized state, since the polycrystalline Ni 3 Al is generally brittle due to the grain boundary (GB) fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous TEM observation revealed that each band had a single brass texture [11]. Thus, two kinds of bands, (110) [-112] and (110) [1][2][3][4][5][6][7][8][9][10][11][12], which were alternately located in the transverse direction, formed the dual Brass textures in total.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed Ni 3 Al foils for high-temperature micro chemical devices [1][2][3][4][5][6]. For the application there are serious concerns about the brittleness in the foils, especially in the recrystallized state, since the polycrystalline Ni 3 Al is generally brittle due to the grain boundary (GB) fracture.…”
Section: Introductionmentioning
confidence: 99%
“…We've recently developed their foils by cold rolling [2][3][4][5][6], which became possible using single crystalline ingots as a starting material [7]. Furthermore, we've found that they exhibit a catalytic activity for hydrogen production reactions such as methanol decomposition [8][9][10][11][12] and methane steam reforming [13,14]. Thus, the Ni 3 Al based foils can be used as a container and a catalyst in the micro chemical reactor for hydrogen production consequently.…”
Section: Introductionmentioning
confidence: 99%